Study of Bacterial Contaminants and some Chemical Elements of the Euphrates River and Al-Fallujah City Drainage - Shaimaa M. Dawd (Indian Journal of Forensic Medicine & Toxicology, 2021)
This article included bacteriological and some chemical elements study of pollution from Euphrates riverand Al-Flalloja city drainage. The study of four selected sites which are Euphrates river (T), Al-Falahat (F)drainage, Al-Ne’emya (N) drainage, and Al-Bo Alwan (B) drainage in the period 11-13/December/2016Bacteria were isolated and diagnosed in water samples depending on their cultural, microscopic biochemicaltests. Results showed that the water samples were polluted with bacteria produced by human and animalwastes, 7out 20 isolates were selected and diagnosed. The study included counting the concentration ofsome chemical ions such as Sodium, Potassium using a flame photometer, the highest concentration ofSodium was in station F and the highest concentration of Potassium was at the station B, concentrations ofcarbonates and bicarbonates were measured using titration method, the highest concentration of bicarbonatesion was at station T, it also showed no carbonates in a water sample